2003
DOI: 10.1163/156856203769231619
|View full text |Cite
|
Sign up to set email alerts
|

Surface treatment of polycarbonate films aimed at biomedical application

Abstract: Aiming to encapsulate pancreatic islets, a biocompatible polycarbonate membrane (Whatman) was treated with plasma argon in order to improve its surface properties. The argon plasma treatment decreased the hydrophobicity of the membrane by fixing polyvinylpyrrolidone (PVP) at the surface. The water angle contact decreased from 47 degrees to 20 degrees after this treatment, while the structure and pore diameter were preserved. The treatment also increased significantly the water permeability from 62 +/- 8 ml/min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Plasma surface modification of polycarbonate films is utilized in a number of applications such as enhancing biocompatibility [9] and improving adhesion between polycarbonate and silicon alloy in protective and optical coatings [10]. It has been observed that plasma treated polymers try to revert back to their original surface properties with time.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma surface modification of polycarbonate films is utilized in a number of applications such as enhancing biocompatibility [9] and improving adhesion between polycarbonate and silicon alloy in protective and optical coatings [10]. It has been observed that plasma treated polymers try to revert back to their original surface properties with time.…”
Section: Introductionmentioning
confidence: 99%
“…In a biological environment, the deposited layer swells and the drug is released during a period of several days. The hydrophilic coating of polyvinylpyrrolidone decreases the bioadhesion of endothelial cells [5] (Fig. 12.5) during implantation in the peritoneal cavity of the rat.…”
Section: In Vivo Implantationmentioning
confidence: 99%
“…Some radicals formed during the plasma treatment would probably react with the polymer film. Surface examination by XPS analysis [5] before and after washing with water (Table 12.3) and even with phosphate detergent (e.g., with one of the solutions usual in hospitals, such as RBS ® detergent, consisting of a mixture of anionic and nonionic surfactants) indicates the presence of PVP coating on the substrate after the washing. These results are also found by ToF-SIMS spectroscopy [6], and lead to the idea of the formation of a thin polymer film covering the surface.…”
Section: Coating With Commercial Native or Synthetic Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…However, PCs have certain drawbacks such as less antibacterial activities, stress cracking, low scratch resistance, high sensitivity to abrasive cleaners, and ability to deteriorate in many organic solvents [18,19]. Generally, the PC's antibacterial activity is being enhanced by functionalizing reactive groups/blending with other antibacterial materials [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%